Basicladia emedii (Cladophorales, Chlorophyta): a new freshwater epilithic species from Brazil - Peres, Cleto Kaveski; Zanini Branco, Ciro Cesar [UNESP] (Adac-cryptogamie, 2012)
Basicladia emedii sp. nov. is described based on material from six streams in Parana and Rio Grande do Sul States of Brazil. This is only the second species of Basicladia recorded from South America. The new species is distinguished based on small filaments with short and wide basal cells of upright axes. It is only the second (out of six) species that is only known with an epilithic habit and is not associated with either snail shells or turtle carapaces.
Keywords: Macroalgae; green algae; filamentous; subtropical; lotic systems; Brazil